Presurgical evaluation of adult thorax-surgery patients with oncologically resectable tumours – a joint recommendation of DGAI, DGT and DGP Die präoperative Evaluation erwachsener thoraxchirurgischer Patientinnen und Patienten mit onkologisch resektablen Lungentumoren – eine gemeinsame Empfehlung der DGAI, DGT und DGP - Defosse, J.; von Dossow, V.; Dudek, Wojciech; Halank, M.; Loop, T.; Stoelben, E.; Westhoff, M. (Anästhesiologie & Intensivmedizin, 2025)
The increasing incidence of malignant lung diseases, neoadjuvant therapies, and the expected detection of operable stages through future lung cancer screening require differentiated preoperative decisions regarding functional operability against the backdground of an in crease in respiratory diseases, especially COPD, but also interstitial lung diseases. Since the postoperative risk of cardiovascular and pulmonary complications after lung resection increases with the extent of lung parenchymal resection and the pre-existing impairment of organ function of the heart, lungs, kidneys, and metabolism, these also require special attention. Given the increasing number of elderly patients over 75 years of age, this also applies to frailty, which represents another key parameter in structured evaluation.
CRIS-Team Scopus Importer:2025-10-31
Keywords: Diagnostics; Lung resection; Preoperative evaluation; Pulmonary tumors; Pulmonology; Thoracic anesthesia; Thoracic surgery